Population-based structural health monitoring of historical masonry bridges using spaceborne InSAR measurements - Wael Alahmad; Said Quqa; Cristina Gentilini (Engineering Structures, 2026)

Crowdsensing-based automated operational modal analysis for indirect bridge structural health monitoring - Eleonora Massarelli; Marco Civera; Samuele Mara; Marco Raimondi; Pier Francesco Giordano; Said Quqa; Mauro Aimar; Maria Pina Limongelli; Bernardino Chiaia (Engineering Structures, 2026)

The value of seismic structural health monitoring for post-earthquake building evacuation - Pier Francesco Giordano; Chiara Iacovino; Said Quqa; Maria Pina Limongelli (Bulletin of Earthquake Engineering, 2022)
In the aftermath of a seismic event, decision-makers have to decide quickly among alternative management actions with limited knowledge on the actual health condition of buildings. Each choice entails different direct and indirect consequences. For example, if a building sustains low damage in the mainshock but people are not evacuated, casualties may occur if aftershocks lead the structure to fail. On the other hand, the evacuation of a structurally sound building could lead to unnecessary financial losses due to business and occupancy interruption. A monitoring system can provide information about the condition of the building after an earthquake that can support the choice between several competing alternatives, targeting the minimization of consequences. This paper proposes a framework for quantifying the benefit of installing a permanent seismic structural health monitoring (S 2 HM) system to support building evacuation operations after a seismic event. Decision-makers can use this procedure to preventively evaluate the benefit of an SHM system and decide about the worthiness of its installation.